HUMAN RESOURCES MANAGEMENT: LEGAL REVIEW OF SEVERANCE PAY DUE TO RETIREMENT OF PENSION AGE - Djuwito Djuwito (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The relationship between workers and employers in a company is very susceptible to problems, one of the most frequent problems when terminating employment at retirement is the calculation of severance pay that must be paid by employers to workers. Law No. 13 of 2003 concerning Manpower regulates pension money for workers who have experienced layoffs because they have met retirement age. The purpose of this research is expected to be donated to enrich the field of law, namely a variety of information for both workers and employers to place severance pay and other rights in the Indonesian labour law system. The approach method used is a normative juridical approach, using the provisions of the prevailing laws and regulations. This type of discussion is carried out in a descriptive analytic manner, on the data collected based on library research.